PERAN MEDIA WAYGROUND DALAM MENINGKATKAN MINAT BELAJAR IPS PESERTA DIDIK KELAS VIII MTS SALAFIYAH - Ai Siti Rohmat; Lili Dianah; Sudarmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of Wayground media in increasing social studies learning interest among eighth-grade students at MTs Salafiyah. This research employed a qualitative method using a library research approach. The research data were obtained from various literature sources such as books, scientific journals, research articles, and other documents related to game-based learning media, learning interest, and social studies learning. Data collection techniques were carried out through documentation studies and literature analysis, while data analysis used content analysis techniques. The results showed that Wayground media plays an important role in creating a more interactive, engaging, and enjoyable social studies learning process. The use of game-based learning media can increase student involvement in learning activities, foster enthusiasm, and reduce boredom toward theoretical social studies materials. In addition, Wayground media helps teachers create more innovative learning environments and encourages students to be more active in discussions and classroom activities. Students’ responses to the use of Wayground media indicated an increase in attention, participation, and learning interest during the learning process. Therefore, Wayground media can be used as an effective alternative learning medium to improve social studies learning interest among eighth-grade students at MTs Salafiyah.